Items from lodgings on Southampton Street. Posthumous inventory of Polish insurgent from 1830 as a reflection of the fate of emigrants - Marchlewicz, Krzysztof (In the Mirror of Things, 2022)
This article is an overview of the posthumous inventory of things belonging to captain Teodor Karol Jeleński, who died of cerebral hemorrhage in London on May 7th, 1836 at the age of thirty-two. The inventory is now kept at Bibliothèque Polonaise à Paris together with other documents related to the history of the Polish political emigration in the United Kingdom. During the November Uprising Jeleński fought against the Russians as an officer in the 20th Infantry Regiment. Then he went into exile and spent the first years of emigration in Saxony. As a result of police repression, he had to seek an asylum in England. The state of his possessions described in the inventory reflects the hardships and difficulties of everyday life of the Polish refugees in London and proves that Jeleński made attempts to supplement his scanty resources by earning as a painter. Among his belongings were also items suggesting that he could still identify himself with the political goals of Polish emigration and he was seeking some kind of consolation in religion.